People Protected Bike Lanes: Global Expansion of an Emergent Cycling Demonstration - Marcel Moran (Findings)
Starting in 2017, a new public demonstration called "People Protected Bike Lanes" (PPBL) took place in San Francisco, in which participants stand on the street in a line between cyclists and car traffic to demonstrate the inadequacy of existing bicycle infrastructure. Between 2017-2023, there were at least 55 PPBL demonstrations in 25 different cities in 11 countries. At more than half of the streets in which PPBL were held, protected bike lanes were later installed. PPBL's straightforward arrangement, legibility to news media, and participants' use of online social networks have likely contributed to its considerable global spread, and influence on bike-lane upgrades.